Busuu Application Aided Instruction in Improving Students Pronunciation - Shinta Bella Puspita; Dyah Sih Pratiwi; Ahmad Syafiq (Journal of English Education, Literature and Linguistics, 2025)
This research aims to determine the effectiveness of the Busuu application in improving the English pronunciation skills of tenth-grade students at MA Muhammadiyah Batuliman, South Lampung. The subjects of this study were 16 students selected through purposive sampling. The research employed a Classroom Action Research (CAR) design conducted in two cycles. Data collection techniques included observation and pronunciation tests, with pre-test and post-test scores analyzed to measure improvement. The results showed an increase in the average score from 62.5 in the pre-test to 70.0 in post-test Cycle I, and 82.3 in post-test Cycle II, indicating a total improvement of 31.68%. The use of Busuu’s audiovisual features and interactive learning environment enhanced students’ motivation, engagement, and confidence in speaking English. Students became more active, independent, and reflective in their learning, with noticeable improvements in word stress, intonation, and rhythm. These findings are consistent with previous studies highlighting the positive impact of mobile-assisted language learning. The study concludes that integrating the Busuu application into English instruction can effectively support pronunciation mastery and foster autonomous learning.Keywords: Busuu Application, Pronounciation, Classroom Action Research